METHODS OF INCREASING THE EFFICIENCY OF LESSONS USING MOBILE EDUCATIONAL TECHNOLOGIES - Mamasoliyev Akmaljon Azizjon oglu (Web of Journals Publishing, 2025)
This article comprehensively analyzes the contribution of mobile educational technologies to the educational process and their role in increasing the efficiency of lessons. Mobile technologies are one of the important tools for introducing modern approaches to education, increasing students' motivation to study, and implementing interactive approaches. The article shows the use of mobile applications, educational platforms, and Internet resources in the educational process. In particular, the role of mobile applications and Internet technologies in increasing students' interest in studying, facilitating and strengthening the process of acquiring knowledge is discussed. The article also highlights the effectiveness of using mobile technologies in measuring the level of students' knowledge, the importance of assessing the pedagogical and psychological impact of mobile educational technologies in implementing interactive lessons and individual approaches. The use of mobile educational technologies to activate students and increase their interest in learning can significantly increase educational effectiveness.
Keywords: Mobile educational technologies, effectiveness of lessons, pedagogical foundations, psychological impact, motivation, interactive approach, individual approach, educational process, student education, computer science, mobile applications, educational platforms, Internet resources, educational effectiveness, student interest.